INFLUENCE OF THE ADOPTION OF MOBILE MONEY PAYMENT STRATEGY ON ORGANIZATION PERFORMANCE OF NANYUKI WATER AND SEWERAGE COMPANY, KENYA - Munjogu, Jesse Njoroge; Namusonge, Dr. Mary (European Journal of Business and Strategic Management, 2017)
Purpose: To establish the influence of mobile money payment strategy on the performance of Nanyuki Water and Sewerage Company. Methodology: The study utilized a descriptive research design. Findings: The findings revealed that perceived ease of use, perceived costs, perceived trust and perceived usefulness have a positive and significant effect on the performance of NAWASCO. This was also supported by the regression results which revealed that perceived ease of use, perceived costs, perceived trust and perceived usefulness had a positive and significant effect n organization performance as supported by a beta coefficient of 0.111 and a p value of 0.004. Unique contribution to theory, practice and policy: The general public will be informed about the influence of adoption of mobile money payment strategy on organization performance. This follows the maxim that "˜information is power' and hence empowers the users as well as providers of the service gearing towards improved services. Nanyuki Water and Sewerage Company will be informed on the influence of adoption of mobile money payment strategy on organization performance. This will enable the management to make relevant adjustments so as to encourage their clients to pay their water bills using mobile money payment. This will make their operations easier and thus result to improved performance. For the policy makers and agencies like the Central bank of Kenya (CBK), the findings of this study will be important in informing the policy formulation especially with regard to regulating the mobile money transfer services. The research findings add dimension that may help improve policy direction with regard to regulation of MMT as well as factors that spur economic growth. As for scholars and academicians, this study will be important in providing information on the influence of adoption of mobile money payment strategy on organization performance. Nevertheless, the research will also suggests areas of further studies where future scholars and researchers can seek more knowledge or better still corroborate emerging theories.